ANALISIS KINERJA PENGANGKUTAN SAMPAH PADA ZONA III KOTA BANDA ACEH (KECAMATAN LUENG BATA, KUTA RAJA DAN BAITURRAHMAN) - Murnianti Murnianti; Syamsidik Syamsidik; Muhammad Zaki (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
The analysis of Waste Transportion Performance in Zone III of Banda Aceh managed to evaluate the waste transport system related to the pattern of waste collection and transportation, the frequency of transportation and the number of waste transport vehicles in zone III, so optimization can be done. Primary data is obtained by observing the process of transporting waste directly in the field and interviewing the parties that involved. Observations were made on each vehicle that carrying waste twice a day (morning and afternoon/night). The vehicles that will be observed consists of 11 dumptrucks, 1 compactor truck, 2 armrolltruck, so the number of observations is 14 days. The application of the pattern of waste collection with the door to door system in some zone III does not match the standards set. The amount of trip for dumptruck can be increased to 3 trips/day, 4 trip/day for compactors truck and 11 trips/day for armroll trucks. Better waste disposal can save dumptruck transportation time 2.18 hours/day or 27.26% and increase ritation to 3 trips/day. The addition of transport trips increases the potential amount of waste transportation up to 59.17% from 48.10 tons/day to 76.56 tons/day. The needs for waste transportation based on the calculation results can be optimized to 10 units, while currently used is 14 units. Inadequate of work equipment, there is no special training for workers and a lack of public awareness in properly disposing waste can be a barrier in waste transportation services.